Effects of Moderate Enzymatic Hydrolysis on Structure and Functional Properties of Pea Protein - Xixiang Shuai; Lizhi Gao; Qin Geng; Ti Li; Xuemei He; Jun Chen; Chengmei Liu; Taotao Dai (Foods, 2022)
Pea protein (PP) was moderately hydrolyzed using four proteolytic enzymes including flavourzyme, neutrase, alcalase, and trypsin to investigate the influence of the degree of hydrolysis (DH) with 2%, 4%, 6%, and 8% on the structural and functional properties of PP. Enzymatic modification treatment distinctly boosted the solubility of PP. The solubility of PP treated by trypsin was increased from 10.23% to 58.14% at the 8% DH. The results of SDS-PAGE indicated the protease broke disulfide bonds, degraded protein into small molecular peptides, and transformed insoluble protein into soluble fractions with the increased DH. After enzymatic treatment, a bathochromic shift and increased intrinsic fluorescence were observed for PP. Furthermore, the total sulfhydryl group contents and surface hydrophobicity were reduced, suggesting that the unfolding of PP occurred. Meanwhile, the foaming and emulsification of PP were improved after enzymatic treatment, and the most remarkable effect was observed under 6% DH. Moreover, under the same DH, the influence on the structure and functional properties of PP from large to small are trypsin, alcalase, neutrase and flavourzyme. This result will facilitate the formulation and production of natural plant-protein-based products using PP.